(untitled) (JED (Jurnal Etika Demokrasi), 2026)
Low critical thinking in elementary Pancasila Education limits students’ capacity to analyze civic problems and make reasoned moral decisions. This study examined the effect of inquiry-based learning on fourth-grade students’ critical thinking skills in Pancasila Education at SD Negeri 20 Palu. A quantitative pre-experimental design with a one-group pretest-posttest procedure was employed. The participants were 26 fourth-grade students selected through saturated sampling. Data were collected using essay-based pretest and posttest instruments and documentation, while instrument quality was confirmed through validity testing and reliability analysis, yielding a Cronbach’s Alpha value of 0.811. Data were analyzed using the Shapiro-Wilk normality test and the Wilcoxon Signed-Rank Test. The findings showed that students’ mean score increased from 56.15 in the pretest to 84.23 in the posttest. The Wilcoxon test produced a significance value of 0.000, indicating a statistically significant improvement after inquiry-based learning. These results demonstrate that inquiry-based learning effectively enhances students’ critical thinking through investigation, discussion, analysis, and conclusion-making. The novelty of this study lies in applying inquiry-based learning within elementary Pancasila Education. Its contribution is to provide an evidence-based pedagogical strategy for strengthening critical civic learning in elementary schools.